ОЧІКУВАЛЬНА СТРАТЕГІЯ У ХВОРИХ НА РАК ПРЯМОЇ КИШКИ З ПОВНОЮ КЛІНІЧНОЮ ВІДПОВІДДЮ ПІСЛЯ НЕОАД'ЮВАНТНОЇ ХІМІОПРОМЕНЕВОЇ ТЕРАПІЇ: ДОСВІД ОДНОГО КЛІНІЧНОГО ЗАКЛАДУ - KOKAINE, L.; RADZINA, M.; LIEPA, M.; GERINA-BERZINA, A.; SĪVIŅA, E.; NIKOLAJEVA, J.; GARDOVSKIS, A.; Miklaševičs , E. (PH Akademperiodyka, 2024)
Background. The non-operative management of rectal adenocarcinoma (RA) after neoadjuvant chemoradiation therapy (nCRT) has gained increasing attention. The “Watch and Wait” (“W&W”) strategy allows one to avoid surgery-related reduction in the quality of life due to permanent pelvic organ dysfunction or irreversible stoma. Still, the oncological safety of this strategy is under evaluation. Aim. To share a single-center experience of the “W&W” strategy. Materials and Methods. The retrospective analysis of 125 patients who received nCRT in 2016—2021 was performed. Patients who met the European Society for Medical Oncology (ESMO, 2017) criteria of clinical complete response (cCR) and received non-operative management were analyzed. Results. Ten patients (8%) were re-staged after nCRT as cCR and followed the “W&W” strategy. Patients’ characteristics: 7 female, 3 male; mean age 67.3 years. Tumor characteristics: pre-treatment N+ was present in 7 cases; G1 adenocarcinoma in a majority of cases; mean tumor distance from the anal verge — 5.85 cm; mean tumor circumference — 71%; mean tumor length — 3.87 cm. The mean follow-up time was 30 months. Local regrowth or/and distant metastases developed in 3 cases. The 2-year disease-free survival was 70%. Conclusions. Most of the patients following the “W&W” strategy have benefited. However, to reduce the number of relapses, it is necessary to perform a more careful selection of patients.